Total rings of fractions and Hermite rings (2020)
In this paper, we show general properties of total rings of fractions and of Hermite rings. We study the relationships between those rings and the finite dimensional K−algebras. A finite dimensional K−algebra is a commutative algebra with unit such that this is finite dimensional as vector space over a field K. We proof that the finite dimensional K−algebras are total rings of fractions and also Hermite rings. In addition, we show that direct product of fields is another example of total ring of fractions and Hermite ring.